ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PENERIMAAN PAJAK PENGHASILAN (Studi Kasus pada Kantor Pelayanan Pajak Pratama Wajib Pajak Orang Priba Di Kota Semarang Tahun 2012-2013) (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the factors that affect the level of income tax revenue the individual tax payer. The data used in this study is the data on the Primary Tax Office in the city of Semarang year 2012-2013 with a total sample of 110 data collection method used is to use secondary data. Data were analyzed using multiple linear regression. The results showed that the tax collection letters and letter Forced Tax positive and significant effecton the level ofincome tax revenue. While the extensification Number of Tax payers and Tax and no significant positive effecton income tax revenue. Keywords: Number of individual taxpayer, extensification Tax, Tax Collection Letter, Letter of Acceptance Levels Forced Tax and Income Tax